2015
DOI: 10.4314/ijbcs.v9i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of tendril and fruit stalk in Curcubitaceae Juss. from Nigeria

Abstract: Comparative anatomy of the fruit stalk and tendril of nine (9) species representing 8 genera of Cucurbits from Nigeria has been carried out to complement the existing taxonomic data on the family. Fresh plant materials from representative members of the genera Zehneria, Luffa, Momordica, Coccinnia, Telfairia, Cucurbita, Lagenaria and Cucumis collected from the wild during field trips to various parts of Nigeria were used for this study. The specimens were wax embedded, sectioned, stained and photographed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
5
11
0
Order By: Relevance
“…However, lignification of the epidermal cells and cells in subepidermal layer in the distal part of the coiled tendril might help to fasten the plant on to the support. In line with the observations of the present study, thick‐walled cells in different regions have been reported in the leaf tendrils of other monocot species (Ekeke et al, 2015; Rjosk et al, 2018). In tendrils of monocots, the adaxial subepidermal cells develop thickening initially to support the tendril and later these cells are sclerified and forms a band around the vascular bundles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, lignification of the epidermal cells and cells in subepidermal layer in the distal part of the coiled tendril might help to fasten the plant on to the support. In line with the observations of the present study, thick‐walled cells in different regions have been reported in the leaf tendrils of other monocot species (Ekeke et al, 2015; Rjosk et al, 2018). In tendrils of monocots, the adaxial subepidermal cells develop thickening initially to support the tendril and later these cells are sclerified and forms a band around the vascular bundles.…”
Section: Discussionsupporting
confidence: 93%
“…In tendrils of monocots, the adaxial subepidermal cells develop thickening initially to support the tendril and later these cells are sclerified and forms a band around the vascular bundles. This provides mechanical strength to the tendrils to anchor the plant during the climbing process (Ekeke et al, 2015; Rjosk et al, 2018). In the previous study, papillate or conical epidermal cells were reported in tendrils of the monocot leaf climber Flagellaria indica L. (Rjosk et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…7h). The results are in harmony with the finding of Ekeke et al (2015) who found that among the different representatives of the genera studied, the shape of the fruit stalk varied from one genus to another the fruit stalk is fairly triangular, 4-angled, 6-angled, 5-angled, irregular and oval or spherical.…”
Section: Anatomical Characters Of Flower Pedicel: Outline Shapesupporting
confidence: 90%
“…The cuticle was smooth in all studied taxa. In male flowers, the cuticle layer varies in thickness from 2.17 The results are in harmony with the finding of Ekeke et al (2015) who found that the nature of epidermis in the fruit stalk had only 1-layer and was predominantly oval in shape.…”
Section: Epidermissupporting
confidence: 87%
“…Anatomical data are useful for characterizing, revealing plant evolution and genetic relationships among species since they are less affected by the environment. The previous study showed that the anatomical characteristics of fruit stalks and tendrils can be used to distinguish among species within Cucurbitaceae (Ekeke et al 2015). Variations of stomatal types among some Cucurbitaceae members are paracytic, diacytic, anisocytic, actinocytic, syclocytic, and staurocytic (Abdulrahaman et al 2011).…”
Section: Introductionmentioning
confidence: 99%